XML for browser-based electronic medical records / Hafizam Mat Hussin - Hafizam, Mat Hussin (2005)
XML for Browser-based Electronic Medical Records is a system that using XML to represent, store and display information that is extracted from existing hospital systems. It is an XML database designed to provide a clinician-centered view of the patient's history, with a web browser as the user interface. Patient records are created and maintained as XML documents within an XML database. Data feeds from the HIS make use of existing HIS interfaces with somen customization to meet the data requirements of the XML patient record database. HIS extracts are triggered by events occuring within the system. As updates take place, the XML database can provide full auditing of transaction that have taken place. The major modules in XML for Browser-based Electronic Medical Records are the administrator module and user module. This report focuses on the administrator module. The administrator module provides support for various administrative tasks, which are controlling user access, memo/message board management, search services and e-mail services. The proposed development tools for this project will take advantage of one the latest technologies, which is XML, Microsoft Access 2003 as the DBMS, Macromedia Dreamweaver MX as development workspace, Windows NT server as the development platform, plus several other tools. This system sees the opportunity in avoiding and rectifying the weaknesses found in existing electronic medical records systems or website and hopes to provide a better solution to the medical field.